Measurements of explosion parameters for diethyl ether/air mixtures at pre-ignition quasi-isotropic turbulence. (15th May 2021) - Wang, Yue; Li, Wenliang; Chang, Qi; Cheng, Jianwei
Highlights: The peak pressures of the DEE/air mixtures reach 0.93 MPa at U rms 6.2 m/s. The largest data of turbulent burning velocity ( u t ) is 1.8 m/s. The model gives the expression on u L and u t . Abstract: This paper presents a detailed investigation of the explosion characteristics (i.e., maximum explosion pressure, maximum rate of the pressure rise) and combustion properties (i.e., laminar burning velocity, turbulent burning velocity) of diethyl ether (DEE)/air mixtures under different pre-ignition quasi-isotropic turbulence velocity. The concentration of DEE/air mixtures is the equivalence ratio ϕ = ~1.1. The experiment is performed by systematically measuring the pressure evolutions in a 20-L explosion spherical vessel. The present measurement shows that the peak explosion pressure (Pmax ) increased nonlinearly with increasing pre-ignition turbulence velocity. The peak pressures reach the maximum values of 0.93 MPa at pre-ignition turbulence velocity 6.2 m/s, and the lowest are 0.57 MPa at pre-ignition turbulence velocity 1.0 m/s. The experimental result of the laminar burning velocity ( u L ) is ~ 0.55 m/s, and the largest data of turbulent burning velocity ( u t ) are 1.8 m/s at pre-ignition turbulence velocity at 6.2 m/s. In this work, the model gives the expression on the laminar burning velocity ( u L ) and turbulent burning velocity ( u t ) versus the pre-ignition turbulence velocity U rms  in accordance with Williams's theoretical model.